2017
DOI: 10.20944/preprints201703.0230.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Support Structures in an LES Actuator Line Model of a Tidal Turbine with Contra-rotating Rotors

Abstract: Abstract:Computational fluid dynamics is used to study the impact of the support structure of a tidal turbine on performance and the downstream wake characteristics. A high-fidelity computational model of a dual rotor, contra-rotating tidal turbine in a large channel domain is presented, with turbulence modelled using large eddy simulation. Actuator lines represent the turbine blades, permitting the analysis of transient flow features and turbine diagnostics. The following four cases are considered: the flow i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The correction is meant to be applied at the angle of attack calculation stage, where the total additional induction from the wake system, w corr , is added to the local relative velocity and the angle Illustration of a vortex system of a translating planar wing of attack value is determined. To apply the correction, the location of the wake vortices and their strengths have to be defined in advance as these are required, see Equation (16). For a translating planar wing application, wake vortices can be assumed to form a straight vortex sheet which is parallel to the flow and which trail from the quarter-chord line of the wing (see Figure 6).…”
Section: Translating Planar Wingmentioning
confidence: 99%
“…The correction is meant to be applied at the angle of attack calculation stage, where the total additional induction from the wake system, w corr , is added to the local relative velocity and the angle Illustration of a vortex system of a translating planar wing of attack value is determined. To apply the correction, the location of the wake vortices and their strengths have to be defined in advance as these are required, see Equation (16). For a translating planar wing application, wake vortices can be assumed to form a straight vortex sheet which is parallel to the flow and which trail from the quarter-chord line of the wing (see Figure 6).…”
Section: Translating Planar Wingmentioning
confidence: 99%
“…The first approach applies a uniform force to the flow, and it is a computationally inexpensive alternative that allows multiple devices simultaneously, but lose the representation of important elements like rotor swirl [14,15,16]. The latter ALMs and models that consider the detailed geometry of the device improve the turbine representation, but require considerably more computational resources, due to computationally expensive interpolations to the grid nodes and therefore have not been used for large turbine arrays, even though they can resolve near-field features and unsteady vortical structures generated by the turbine geometry [17,18,19,20,21,22,23].…”
Section: Take Down Policymentioning
confidence: 99%
“…To capture dynamically-rich turbulent coherent structures in the wakes, more advanced but expensive models based on large-eddy simulations (LES) can provide accurate descriptions of these flow fields, yielding detailed solutions by resolving directly all the turbulent scales larger than the size of the computational grid. This produces information on the flow unsteadiness, turbulence, and vortical structures, and therefore it has been used to study tidal turbines, but limited to few devices due to its larger computational cost [16,17,18,19,22,23].…”
Section: Take Down Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Combining TPMs with mesh-optimization techniques was first considered by Creech et al, 9 and more recent implementations can also be found in Abolghasemi et al, 10 and Creech et al 11 each employing a different TPM (actuator volume and actuator disk and actuator line based, respectively).…”
mentioning
confidence: 99%